Day 2 Wed, February 10, 2016 2016
DOI: 10.2118/179139-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improving North Sea Fracturing and Stimulation Economics Through Increasing Innovation and Efficiency in Operations and Applications: Lessons Learned

Abstract: Completion and intervention costs across the North Sea are at an all-time high and continue to challenge development economics; this has been exacerbated recently by a deteriorating oil price making costeffective completion and intervention operations even more challenging. Typically at times such as these, the industry turns to the fracturing and stimulation process to maximise the return from existing assets and new wellbores. While this method continues to be feasible, increasingly this can only be achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In late 2013 these treatments were performed (Ishteiwy et al, 2016) and the results can be seen in Table 1. It was surmised that the use of StressCage had resulted in substantial near wellbore formation damage, and, therefore, a suite of acid, diversion and scouring stages would be able to address this.…”
Section: Injection Behaviourmentioning
confidence: 99%
“…In late 2013 these treatments were performed (Ishteiwy et al, 2016) and the results can be seen in Table 1. It was surmised that the use of StressCage had resulted in substantial near wellbore formation damage, and, therefore, a suite of acid, diversion and scouring stages would be able to address this.…”
Section: Injection Behaviourmentioning
confidence: 99%
“…Therefore, it is necessary to achieve design goals through optimizing operating procedures. Ishteiwy et al (2016) indicated that creative operational solutions must be constantly sought to facilitate the development of increasingly difficult reserves through stimulation operations. However, there are currently few relevant explanations to reveal the mechanism of HF geometry control and elaborate on how to formulate an optimal injection strategy to maximize SRV for tight heterogeneous glutenites.…”
Section: Introductionmentioning
confidence: 99%